2011
DOI: 10.1111/j.1478-3231.2011.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase proteins in the diagnosis and prediction of cirrhosis associated bacterial infections

Abstract: C-reactive protein on its own is a sensitive screening test for the presence of bacterial infections in cirrhosis and is also a useful marker to predict the likelihood of clinically significant bacterial infections in patients without overt infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 35 publications
9
81
0
6
Order By: Relevance
“…Additionally, there was a significant difference in ascitic fluid, but not serum, PCT levels when comparing the cardiac cirrhosis/miscellaneous subgroup to other subgroups. This study also demonstrated that PCT levels have no relationship with serum or ascitic fluid total leukocyte or monocyte levels, supporting data of its inflammatory expression pattern in multiple nonhematologic organ sites [19,20] . As there was no cohort group with infection studied, no conclusion as to its discriminatory capacity between sepsis and SIRS can be made.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Additionally, there was a significant difference in ascitic fluid, but not serum, PCT levels when comparing the cardiac cirrhosis/miscellaneous subgroup to other subgroups. This study also demonstrated that PCT levels have no relationship with serum or ascitic fluid total leukocyte or monocyte levels, supporting data of its inflammatory expression pattern in multiple nonhematologic organ sites [19,20] . As there was no cohort group with infection studied, no conclusion as to its discriminatory capacity between sepsis and SIRS can be made.…”
Section: Discussionsupporting
confidence: 62%
“…The serum-ascites gradients of these inflammatory markers lends further support to the complex periperitoneal interplay of BT and immunocyte activation in both non-infected and infected cirrhotic patients with ascites [16][17][18][19][20]29] . It is interesting to speculate on the particular importance of ascites itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Indeed, cirrhotic patients, even if not infected, often present hypotension and hyperdynamic circulatory state, have low white blood cell count as a result of hypersplenism, and may exhibit a reduced production of acute-phase proteins, especially C-reactive protein, in response to infection. 50,51 In a study enrolling patients with ACLF admitted to ICU, SIRS was not an independent factor for mortality at multivariate analysis. 52 Other well-known scores for BSI severity, such as the Pitt score has not been validated in the LC population, but probably could have many of the same limitations of sepsis score, being based on fever, hypotension, mechanical ventilation, cardiac arrest and altered mental status.…”
Section: Clinical Findings and Complicationsmentioning
confidence: 99%
“…However Cervoni reported that in patients with decompensated cirrhosis (with or without infection), persistently elevated CRP concentration predicted short-term mortality independent of MELD score, and was superior to the clinicallyassessed SIRS [37]. Also, Papp et al [38] reported that CRP was a reliable marker of bacterial infection in patients with cirrhosis, although its accuracy decreased in advanced cirrhosis or in the presence of ascites.…”
Section: Discussionmentioning
confidence: 99%